Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages community are also specially dangerous. It is essential that men should enter them and desirable therefore, that they should be able to do so with the assurance of special provision against their risks." We are doubtful, however, if the recommendations of the Report carry out this principle consistently. The existing benefits under workmen's compensation for total disablement are: for earnings of 50/- per week upwards, a weekly payment not exceeding 30/- plus 3/- war-time supplementary allowance and children's allowances of 4/- for the first child and 3/- for each subsequent child. A wife receives, should her husband be killed, £200 or three years' earnings — whichever is the higher — up to a maximum of £300. There is also a payment for children of men who have been killed, varying with the child's age and the workers' earnings. The Beveridge Report makes the following proposals:— (3) [(1)] During the first 13 weeks the worker will get the same as he would if on sickness disability benefit, i.e. 24/- single man, 40/- man and wife, and 8/- for each child. (2) After the first 13 weeks, the worker on total disablement benefit will be entitled to two-thirds of previous earnings up to a maximum of £3 plus children's allowances. (3) There would be a lump sum payment to a widow, though the amount of this would be considered in relation to her widow's and guardian's pension. All workers who are disabled for longer than 13 weeks will be much better off under the Beveridge scheme than they are at present. Not so some of those whose disablement lasts less than 13 weeks. Take a single man earning £3 10s. per week. Under the existing scheme he would get 35/- per week. Under the Beveridge 17 15X/2/103/272